Response of bacterial community structure to different phosphorus additions in a tobacco-growing soil - Zhou, Beibei; Cheng, Shiqian; Peng, Shuang; Li, Wenqing; Li, Chunying; Wang, Qianqian; Wang, Yiming; Guo, Jinping (Frontiers in Plant Science, 2024)
Phosphorus (P), which plays a vital role in plant growth, is continually added to soil to maximize biomass production, leading to excessive P accumulation and water eutrophication. In this study, a pot experiment using a subtropical tobacco-growing soil fertilized with four P levels-no P, low P, medium P, and high P-was conducted and both rhizosphere and bulk soils were analyzed. P addition significantly increased tobacco biomass production (except under low P input) and soil total P and available P contents (P<0.05), whereas total nitrogen contents decreased in the rhizosphere soils, although this was only significant with medium P application. P fertilization also significantly altered bacterial communities of rhizosphere soils (P<0.05), but those of bulk soils were unchanged (P>0.05). Moreover, a significant difference was found between rhizosphere soils with the low (LR) and high (HR) P inputs (P<0.05). Additionally, compared to rhizosphere soils with no P (CKR), Shannon diversity showed a declining trend, which was significant with LR and HR (P<0.05), whereas an increasing tendency was observed for Chao1 diversity except in LR (P>0.05). Functional prediction revealed that P application significantly decreased total P and N metabolism of microorganisms in rhizosphere soils (P<0.05). Collectively, our results indicate that maintaining sustainable agricultural ecosystems under surplus P conditions requires more attention toward motivating potential of soil functional microbes in P cycling, not just by continual P input.